Database Systems for Advanced Applications DASFAA 2015 International Workshops, SeCoP, BDMS, and Posters, Hanoi, Vietnam, April 20-23, 2015, Revised Selected Papers - Liu, An; Ishikawa, Yoshiharu; Qian, Tieyun; Nutanong, Sarana; Cheema, Muhammad Aamir (Information Systems and Applications, incl. Internet/Web, and HCI, 2015)
DASFAA is an annual international database conference, located in the Asia-Pacific region,which show cases state-of-the-art R & D activities in databases-terms and their applications. It provides a forum for technical presentations and discussions among database researchers, developers and users from academia, business and industry. DASFAA 2015 the 20th in the series, was held during April 20-23, 2015 in Hanoi, Vietnam. In this year, we carefully selected two workshops, each focusing on specific research issues that contribute to the main themes of the DASFAA conference. This volume contains the final versions of papers accepted for the two workshops: Second International Workshop on Semantic Computing and Personalization (SeCoP 2015); Second International Workshop on Big Data Management and Service (BDMS 2015); and a Poster Session. [All the workshops were selected via a public call-for-proposals process. The workshop organizers put a tremendous amount of effort into soliciting and - lecting papers with a balance of high quality, new ideas and new applications. We asked all workshops to follow a rigid paper selection process, including the procedure to ensure that any Program Committee members are excluded from the paper review process of any paper they are involved with. A requirement about the overall paper acceptance rate of no more than 50% was also imposed on all the workshops.].